ANALISIS KEMAMPUAN MEMBEDAKAN MORFEM DAN KATA PADA MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA MANDARIN ANGKATAN 2016 UNIVERSITAS TANJUNGPURA - Fauziah, Rika; Ina, Ina; Khiong, Bun Yan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractWords and morphemes are the most important parts of vocabulary learning. These two language units are closely related, but they have different boundaries. The similarity of the two words often makes it difficult for learners of Chinese to distinguish between meaningful morphemes, morphemes and non-morphemes. Therefore, it is easy to make mistakes and identify them.In order to understand the distinguishing ability of morphemes and words among the 2016 Chinese students of the Tanjungpura University Faculty of Teacher Training and Education,the author used the test method to test the students and analyzed the difficulties of morphemes and words. The test results showed that the students'ability to distinguish words is very good, the correctness rate is 86%, while the students' ability to distinguish morphemes is not good, the correctness rate is only 56%. When analyzing the difficulties, the author finds that most of the problems arise in identifying one morpheme and more than two words.Â Key words:Distinguishing Ability, Morpheme, Word